Desain dan Analisis Antena Mikrostrip Rectangular Dengan Slot “ m ” Untuk Aplikasi WLAN 2,4 GHZ - Nurista wahyu Kirana (Universitas Islam Lamongan, 2021)
Microstrip is being developed in various wireless applications, one of them is the WLAN (Wireless Local Area Network). In this study,